Rapid and Sensitive UPLC-MS/MS Method for Simultaneous Quantification of Peimine and Peiminine: A Multiple Drug Resistance Reversal Agent of Tumors and their Application to Preliminary Pharmacokinetic Studies in Beagle Dogs - Huang, Kun; Liu, Bin; Hu, Kai-Wen; An, Chao; Diao, Yu-Lin; Xu, Jing-Jing (Asian Journal of Chemistry, 2013)
To establish a more comprehensive and suitable UPLC-MS/MS quantitative procedure for pharmacokinetic study of peimine and peiminine, which can be used as reversal agent of tumor multiple drug resistance, in beagle dogs. The analytes were extracted from dog plasma via solid-phase extraction method, with tetrahydropulmatine as internal standard. The chromatographical separation was accomplished on an ACQUITY UPLCTM BEH C18 column (50 mm × 2.1 mm i.d., 1.7 μm) with a gradient mobile phase of acetonitrile and water (10 mmol/L ammonium bicarbonate using ammonia water adjusting pH = 10) at a flow rate of 0.25 mL/min. The identification and detection of target compounds were achieved under multiple reactions monitoring mode with positive electrospray ionization. The linear ranges of the calibration curves for peimine and peiminine are 1-600 ng/mL (r2 > 0.99). The specificity, precision, accuracy, extraction recovery, matrix effect and stability were all in the acceptable ranges. The procedure established herein is more sensitive, specific and validated for the quantitation of peimine and peiminine in dog plasma and can be successfully applied to pharmacokinetic study in beagle dogs.